A self-template and KOH activation co-coupling strategy to synthesize ultrahigh surface area nitrogen-doped porous graphene for oxygen reduction. Issue 77 (2nd August 2016) - Zhou, Huang; Zhang, Jian; Zhu, Jiawei; Liu, Ziyi; Zhang, Chengtian; Mu, Shichun
Abstract : Herein, a self-template strategy is developed to synthesize nitrogen doped porous graphene (NDPG) by using porous biomass as a template, fully coupled with KOH activation. As a catalyst, NDPG exhibits outstanding ORR activity and stability. Abstract : It is highly desirable but challenging to develop a facile strategy to synthesize nitrogen-doped porous graphene with ultrahigh surface area as well as advanced oxygen reduction activity to replace Pt based catalysts due to their high cost, stability and fuel crossover effect problems. Herein, a novel self-template strategy is developed to synthesize nitrogen doped porous graphene (NDPG) by using porous biomass with an abundant plate-like structure as a template, fully coupled with potassium hydroxide (KOH) activation, and followed by nitrogen doping by ammonia (NH3 ) injection. It is worth noting that, unlike the typical CVD method, during the synthesis process, no extra metal catalysts are introduced to form graphene. As a catalyst, the as-prepared NDPG exhibits outstanding ORR activity and stability. The half-wave potential is 10 mV higher than that of Pt/C in alkaline media and the stability is superior to Pt/C in both acidic and alkaline media. The superb catalytic performance of the formed graphene can be attributed to its mesoporous structure with an ultrahigh surface area (∼1969 m 2 g −1 ) as well as the high electron conductivity of the graphene structure and efficient nitrogen content.